PENGARUH DOLOMIT DAN FOSFAT TERHADAP KOMPONEN PERTUMBUHAN, KOMPONEN HASIL DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) VARIETAS HYPOMA 1 - Nurlaela, Lela; Tadjudin, Endang; Subandi, Subandi (Agroswagati : Jurnal Agronomi, 2023)
This study aimed to examine the effects of dolomite and phosphate fertilizers on the growth components, yield components, and overall yield of peanut plants (Hypoma 1 variety), to determine the optimal dolomite and phosphate combination for maximizing growth and yield, and to investigate the correlations between growth components, yield components, and final yield. The experiment was conducted from May to September 2022 at the Al-Zaytun Experimental Garden, Mekarjaya Village, Gantar Subdistrict, Indramayu Regency, West Java, at an altitude of 493 meters above sea level. The soil at the study site was classified as alluvial with a pH of 5.5 and a texture of sandy clay loam. The research employed a Randomized Complete Block Design (RCBD), consisting of 16 combinations of dolomite and phosphate fertilizers, each replicated twice, for a total of 32 plots. The treatments included combinations of dolomite at 0, 250, 500, and 750 kg/ha with phosphate at 75, 100, 125, and 150 kg/ha. The results indicated that different combinations of dolomite and phosphate significantly affected plant height at 28 days after sowing (DAS), number of leaves at 28 DAS, leaf area index at 28 DAS, number of branches at 21 and 28 DAS, root volume at 21 and 28 DAS, plant growth rate, number of pods per plant, number of filled pods per plant, wet and dry pod weight per plant, wet and dry pod weight per plot, and 100-seed dry weight. The highest dry pod yield was obtained from the combination of 500 kg/ha dolomite and 125 kg/ha phosphate (treatment K), which produced 2.54 kg/plot, equivalent to 3.39 t/ha on 80% of optimal land. However, the treatments did not significantly influence plant height at 14 and 21 DAS, number of leaves at 14 and 21 DAS, leaf area index at 14 and 21 DAS, number of branches at 14 and 21 DAS, root volume at 14 DAS, or the number of empty pods.